'Awed listening': H. P. Lovecraft in classic and contemporary audio horror. Issue 1 (1st April 2022) - Hand, Richard J.
From the beginnings of radio drama to digital podcasting, horror has been a significant genre. Radio located an immediate and effective affinity with horror, exploiting the form's qualities of invisibility, immersivity and suggestion in realizing the genre in on-air performance. As a part of this, adaptation ‐ from Gothic classics to populist fiction ‐ has been central. One conspicuous absence in early radio is H. P. Lovecraft with only one notable adaptation in the 1930‐1950s 'golden age'. Nevertheless, in the radio work of Lovecraft acolyte Robert Bloch as well as shows such as Quiet, Please (1947‐49) the 'Lovecraftesque' is strongly evident. Indeed, various dimensions to Lovecraft's fiction make his oeuvre ideally suited to audio adaptation. In recent times, the transmedia pre-eminence of Lovecraft is evident in audio culture as much as anywhere else. This article scopes the presence of Lovecraft in both classic and contemporary contexts of horror audio.